The Effect of Perceived Risk and Perceived Usefulness on Purchase Intention with Customer Attitude as a Mediation Variable (Survey of Tokopedia Consumers in Padang City) - Muhammad Abdul Hadi; Eri Besra; Verinita (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the effect of perceived risk and perceived usefulness on purchase intention with customer attitude as a mediating variable(Survey OnTokopedia consumers in the city of Padang). The type of research used in this research is explanatory research, with the research method being an explanatory survey that emphasizes quantitative methods. The sample is 170 consumers who shop online at Tokopedia in the city of Padang. The sampling technique is purposive sampling. The data analysis method used Structural Equation Modeling - Partial Least Square (SEM-PLS). The results showed that perceived risk had no significant effect on purchase intention. Perceived usefulness has no significant effect on purchase intention. Perceived risk has no significant effect on customer attitude. Perceived usefulness has a significant effect on customer attitude. Customer attitude has a significant effect on purchase intention. Perceived risk has no significant effect on purchase intention mediated by customer attitude. Perceived usefulness has a significant effect on purchase intention mediated by customer attitude.